Bank efficiency and intellectual human capital in Malaysia / Assoc. Prof. Dr. Rosita Haji Suhaimi ... [et al.]. - Suhaimi, Rosita; Ibrahim, Nurhani Aba; Chong, Fen Nee (2010)
In the era of liberalization and globalization, commercial banks are expected to face stiff competition that forces them to be more efficient in controlling their costs. Hence, this study aims to investigate the cost efficiency of the commercial banks in Malaysia, and the significant factors that can influence the cost efficiency of these banks. The Stochastic Frontier Approach was applied to estimate cost efficiency of the banks, which was then regressed as the dependent variable, and competition, ICT infrastructure, intellectual human capital, and size of the commercial banks were the independent variables. This study includes all the 23 commercial banks in Malaysia from 1990 to 2009. Most of the time since 1995, the cost efficiency of foreign banks has surpassed the cost efficiency of the local banks but the local banks seemed to improve their cost efficiency after their merger exercises.